Community Pharmacy/Hospital Based Assessment of Clinical Pharmacist Intervention for Safe and Effective Drug Use - Awofisayo Sunday Olajide, Aboyarin Oladayo, Udoh Imo Emmanuel (Journal of Applied Pharmaceutical Science)
The purpose of the work was to evaluate the extent of interception of prescriptions requiring review for drug order that could have led to adverse drug events or irrational drug use in the community and public hospital pharmacy unit. Three government hospitals and community pharmacy outlets in Ikot Ekpene senatorial district in Akwa Ibom state, Nigeria were selected for the study which lasted 4 months. The pharmacists in the various units were inducted into the purpose of the work and the associated documentation processes. The data collected were patient’s details, reasons for the intervention, doctor’s contact details. The years of experience of the pharmacists in the community was significantly higher than those in the hospital setting in the study (P
Keywords: Pharmacist' s intervention, community pharmacy, government hospital.